Summary of numerical noise studies for Electron-Ion Collider strong-strong beam-beam simulation. Issue 1 (1st January 2023) - Luo, Y; Xu, D; Hao, Y; Qiang, J; Berg, J S; Blaskiewicz, M; Fischer, W; Gamage, R; Gu, X; Huang, H; Hoffstaetter, G; Kewisch, J; et al.
Abstract: The Electron-Ion Collider (EIC) presently under construction at Brookhaven National Laboratory will collide polarized high energy electron beams with hadron beams with design luminosities up to 1 × 10 34 cm −2 s −1 in center mass energy range of 20-140 GeV. We studied the planned electron-proton collisions using a Particle-In-Cell (PIC) based Poisson solver in strong-strong beam-beam simulation. We observed a much larger proton emittance growth rate than in weak-strong simulation. To understand the numerical noise and its impact on strong-strong simulation results, we carried out extensive studies to identify all possible causes for artificial emittance growth and quantify their contributions. In this article, we summarize our study activities and findings. This work will help us better understand the simulated emittance growth and the limits of the PIC based strong-strong beam-beam simulation.